Geologia e geomorfologia dos recifes de Maracajaú-RN e plataforma rasa adjacente - Lima, Williams da Silva Guimarães (2002)
This work focuses the geological and geomorphological characterization of the inner shelf in the West Coast of the Rio Grande do Norte state, particularly the reef coral barrier offshore of Maracajaú (Maxaranguape district). If developed without the necessary concerns, tourism and entertainment activities that have been widely increased during the last five years can lead to irreversible environmental damages to the biotic and abiotic ecosystems of the region. Regarding these aspects, it is crucial the realization of a detailed study to envisage the achievement of a self-sustainable development, especially with respect to the possibilities of a rational usage of the region. This is the aim of this manuscript, which consisted of an initial stage of digital modeling of the terrain with basis on digitalization and vectorization of the Nautical map number 803 (Naval Service of Brazil, 1971). Information obtained in this phase was improved with the digital processing of small format aerial photos acquired from six flights, which were integrated to form a photomosaic of the area. The refined maps produced with the data from Nautical and aerial photo-interpretations aided to locate 9 bathymetric profiles, which provided information about the sea floor relief of the whole area. This later aided in the choosing of areas to bottom sampling that, in its turn, helped to characterize sediments present in floor of the inner shelf. Sixty-four samples collected during this work were studied by granulometrical and chemical analysis; with the later one developed in order to measure carbonate and organic matter contents. Forty-two of these samples showed carbonate content higher than 80% and organic matter in the range of 0.58% to 24.06%. With respect to grain size, these samples are in the interval between fine- to mid-grained sands. Sands with grain sizes higher than this one are also composed by carbonate carapaces such as pale yellow to red rhodolites with ellipsoidal and spheroidal shapes. During determination of the submerse features, the small format aerial photos demonstrated to be a useful methodology to aid the delineation of the sea floor topography through shallow deep waters. The bathymetry, for its turn, revealed several features at the bottom of the platform, in which the most conspicuous are undulations and morphological details of the São Roque Channel. Examination of bottom, aside from sand, yielded the identification of bivalves, ostracods, fragments of bryozoans, spikes of sponges, spines of echinoderms, operculum of gastropods and foraminifers. From the above it is concluded that the multi-methodological approach developed in this study worked efficiently, permitting the geomorphological and environmental characterization of the inner shelf of the North Maracajaú